La diplomacia ciudadana en los noventa: espacios multilaterales como espacio de interacción ciudadanía-gobiernos - Cruickshank, Susana (Revista Mexicana de Política Exterior, 2022)
The structural adjustment policies imposed by international financial bodies following the Washington Consensus and the free market paradigm brought about stagnation, the polarization of wealth and the violation of people’s basic human rights. During the 1990s, social movements and citizens’ organizations began to shift their demands from national institutions to these international bodies, given that national economic policy decisions were being taken in the international arena. This led to the emergence of what some analysts have called citizen diplomacy. At present, only few organizations and movements are not contributing to bringing about changes in international bodies, through their discourse and their policies. What scenarios are envisioned for citizen diplomacy in view of the constant change to the Nation State? What challenges are faced by non-government movements and organizations and the international networks they form part of? In this article, Susana Cruickshank answers these questions and offers a reflection on the forms of articulation, mechanisms and strategies created by international organization and movement networks in the face of power held in international institutional platforms such as the wb, the idb, the wto and the Conference of the Parties of the United Nations on Climate Change.